Epidemiology of Depression and Help-Seeking Behavior, 1979-1983, Los Angeles, California - Aneshensel, Carol S. ([Verlag nicht ermittelbar], 2010)
This project examined the epidemiological distribution of depression in a large metropolitan area. It employed structural equation models to examine the role of stress and social support systems in the occurrence of the condition. Other analysis focused on the antecedents of help-seeking. Using a multistage cluster sample, a probability sample of 1,003 adults (aged 18 and older), a representative sample of the Los Angeles County population, was interviewed in 1979. Three follow-up interviews were conducted over the next year, with an additional fifth interview in 1983. The study has been divided into five parts identified as: Time1, Time2, Time3, Time4, and Time5. Time1 focuses on demographic information, such as marital status, employment status, education, family relationships, household information, sex, and ethnicity. The other main focus of Time1 was on respondents' general health condition and their health insurance. Time2, Time3, Time4, and Time5 focus on diagnostic aspects of depression, social support, the role of stress, in addition to asking respondents questions regarding their behavior and mood, environmental and employment changes, and major life events.